ANALISIS GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA SISWA KELAS III SD NEGERI 1 TUNJUNGAN KABUPATEN BLORA - Oqik April Liyanti April; Mei Fita Asri Untari; Ervina Eka Subekti (STKIP Subang, 2023)
This study was motivated by the learning carried out SD Negeri 1 Tunjungan during Covid 19 is carried out online so that School Literacy Movement cannot be carried out.This literacy practice made students less interested in reading,lazy to learn to read. Early of 2023 the school literacy movement began to be implemented again SD Negeri 1 Tunjungan Study aims to determine the implementation of School Literacy Movement at the habituation stage SD Negeri 1 Tunjungan to find out the impact of the School Literacy Movement on students' interest in reading SD Negeri 1 Tunjungan.study uses a qualitative method.By using observation,interview,questionnaire and documentation.subjects of study class III students SD Negeri 1 Tunjungan.Data was processed by triangulation technique.Triangulation techniques is used to test the credibility of data which is done by checking the data that has been obtained from the same source using different techniques.results showed that the implementation of the school literacy movement SD Negeri 1 Tunjungan has been running well.This is evidenced by the results of distributing questionnaires,documentation and interviews with class III teachers and principals.Results of the questionnaire calculation of students' reading interest show the percentage of indicators of students' needs reading 91%,action find readings 81%, the pleasure reading 90%,the desire always read 75%, following what has been read 72%.Based on the results of study,the suggestion that can be concluded is schools improve facilities and infrastructure that support School Literacy Movement activities such as reading corners,libraries and reading books that can attract students to increase students' interest in reading.